Metal responsive transcription factor 1 (MTF-1) regulates zinc dependent cellular processes at the molecular level - Grzywacz, Agata; Gdula-Argasińska, Joanna; Muszyńska, Bożena; Tyszka-Czochara, Małgorzata; Librowski, Tadeusz; Opoka, Włodzimierz (Acta biochimica Polonica, 2015)
Metal responsive transcription factor 1 (MTF-1) is a zinc dependent transcription factor which is involved in the regulation of intracellular signaling pathways. MTF-1 regulates the expression of two streams of genes functioning in metal homeostasis and anti-oxidative response. MTF-1 acts in the process of binding of toxic metal ions in the cell, due to the activation of the expression of metallothioneins (MTs). Additionally, MTF-1 regulates transcription of genes involved in the sequestration of zinc and its intracellular transport. Disruption of zinc and MT homeostasis has an indispensable influence on the development of several pathological states. Moreover, by increasing MT activity, MTF-1 can effectively protect cells from oxidative and hypoxic stresses. The mechanism of MTF-1 action in cells includes the regulation of the proper immune response through activation/repression of anti- and pro-inflammatory cytokines. MTF-1 function in immune response is related to nuclear factor-κB (NF-κB) activity. Synthesis of insulin is also related to the activity of this transcription factor and zinc balance. Insulin transport also depends on zinc. In pancreatic β-cells, several types of the zinc transporters are found. Zinc transporters coordinated action is crucial for the synthesis and secretion of insulin. Disturbances in the regulation of signaling pathways connected with MTF-1 function can entail further alterations in zinc intracellular status and this growing imbalance can promote the pathophysiology of degenerative disorders.